PEMETAAN GERAKAN PEREMPUAN DI INDONESIA DAN IMPLIKASINYA TERHADAP PENGUATAN PUBLIC SPHERE DI PEDESAAN - Tyas Retno Wulan (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Long history of woman movement in Indonesia showing what woman has given special nuance to democratization learningin Indonesia. Indonesian woman movement dynamic in last two year show that they courageous to express issues about their interest.However, in reality, still much homework to enhance woman access and control in decision making at public sphere that influencingindividual life at family. We have to acknowledge that, woman movement still urban bias and only enjoyed by educated ones. Suburban orvillage woman that became largest part of Indonesian people not yet having access and control to became part of democratization process,so woman have room to own autonomy of herself on public sphere that impendent from other domination. At this point, empowerment andstruggle to bring village woman software they can develop themselves, is an urgent agenda